Product Development of Purple Sweet Potato Mixed with Shallots Jam - Sinthusumran, Sirima; Sai-Ut, Samart; Chotphruethipong, Lalita; Pongsetkul, Jaksuma; Fuangpaiboon, Nattavong; Chunkra, Apiradee (Burapha Science Journal, 2026)
Shallots and purple sweet potatoes often encounter the falling prices situation, thus their processing as the new product helps to increase the value-added. The purpose of this research was to study the ratios of pounded shallot to mashed purple potato for jam production, the quantity of pectin, and the chemical and physical characteristics of the developed jam. Firstly, the optimum formulation for preparation of jam from purple sweet potato and shallot was sensorial evaluated using a 9-pointed hedonic scale. The result was found that the highest sensory acceptance score by the panelists (n = 30) was observed in jam containing purple sweet potato and shallot in the ratio of 25:75 (w/w). Furthermore, adding of 2% pectin in the selected formulation received significantly higher sensory scores for texture and overall acceptability than other samples (p <0.05). The optimum formulation of purple sweet potato and shallot jam consisted of crushed shallots, mashed purple potatoes, water, sugar, lime juice, salt and pectin in amounts of 8.29%, 24.87%, 33.16%, 31.17%, 0.50%, 0.01% and 2.00%, respectively.